Rocaglates as Antivirals: Comparing the Effects on Viral Resistance, Anti-Coronaviral Activity, RNA-Clamping on eIF4A and Immune Cell Toxicity - Wiebke Obermann; Alexandra Friedrich; Ramakanth Madhugiri; Paul Klemm; Jan Philipp Mengel; Torsten Hain; Stephan Pleschka; Hans-Guido Wendel; Roland K. Hartmann; Susanne Schiffmann; John Ziebuhr; Christin Müller; et al. (Viruses, 2022)
Rocaglates are potent broad-spectrum antiviral compounds with a promising safety profile. They inhibit viral protein synthesis for different RNA viruses by clamping the 5′-UTRs of mRNAs onto the surface of the RNA helicase eIF4A. Apart from the natural rocaglate silvestrol, synthetic rocaglates like zotatifin or CR-1-31-B have been developed. Here, we compared the effects of rocaglates on viral 5′-UTR-mediated reporter gene expression and binding to an eIF4A-polypurine complex. Furthermore, we analyzed the cytotoxicity of rocaglates on several human immune cells and compared their antiviral activities in coronavirus-infected cells. Finally, the potential for developing viral resistance was evaluated by passaging human coronavirus 229E (HCoV-229E) in the presence of increasing concentrations of rocaglates in MRC-5 cells. Importantly, no decrease in rocaglate-sensitivity was observed, suggesting that virus escape mutants are unlikely to emerge if the host factor eIF4A is targeted. In summary, all three rocaglates are promising antivirals with differences in cytotoxicity against human immune cells, RNA-clamping efficiency, and antiviral activity. In detail, zotatifin showed reduced RNA-clamping efficiency and antiviral activity compared to silvestrol and CR-1-31-B, but was less cytotoxic for immune cells. Our results underline the potential of rocaglates as broad-spectrum antivirals with no indications for the emergence of escape mutations in HCoV-229E.